A classification of cultural engagements in community technology design: introducing a transcultural approach - Heike, Winschiers-Theophilus; Tariq, Zaman; Stanley, Collin (Springer London, 2017)
Community technology design has been deeply affected by paradigm shifts and dominant discourses of its seminal disciplines, such as Human Computer Interaction, Cultural and Design theories, and Community Development as reflected in Community Narratives. A particular distinction of community technology design endeavours has been their cultural stance, which directs the agendas, interactions, and outcomes of the collaboration. Applying different cultural lenses to community technology design, shifts not only practices but also directs the levels of awareness, thereby unfolding fundamentally distinct cultural engagement approaches. Previous community technology design research indulged in cross-, inter-, and multicultural approaches to community engagement; it was occupied with meticulously deconstructing and reconstructing perspectives, interactions, roles, and agendas. We argue that when deeply immersed in joint design activities in long-term collaborations, we look beyond individual cultures and enter a transcultural mode of engagement. A transcultural community technology design endeavour supports a continuous creation and re-creation of new meanings, originating from individual entities yet being diffused and continuously reflected within the existing design space. We suggest that within community technology design, a context with abundant cultural diversity, a heightened awareness becomes a necessity. We exemplify different instantiations of the cultural engagement approaches within our long-term collaborations and technology design projects with indigenous communities in Malaysian Borneo and Namibia. A transcultural approach to indigenous knowledge preservation and digitisation efforts with indigenous communities opens up a controversial debate about protecting versus integrating local epistemologies. © 2017 Springer-Verlag London Ltd.